2018
DOI: 10.1111/anu.12860
|View full text |Cite
|
Sign up to set email alerts
|

Insect-based diets high in lauric acid reduce liver lipids in freshwater Atlantic salmon

Abstract: We evaluated the effect of a diet containing insect meal and insect oil on nutrient utilization, tissue fatty acid profile and lipid metabolism of freshwater Atlantic salmon (Salmo salar). Insect meal and insect oil from black soldier fly larvae (Hermetia illucens, L.; BSF), naturally high in lauric acid (12:0), were used to produce five experimental diets for an eight-week feeding trial. 85% of the dietary protein was replaced by insect meal and/or all the vegetable oil was replaced by one of two types of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 55 publications
(96 reference statements)
7
53
0
Order By: Relevance
“…A similar trend was observed in studies of Jian carp [ 55 ] and rainbow trout [ 13 ], fed H. illucens larva meal. The positive effect on HSI observed in the present study could be related to reduction of lipid storage in liver, as was demonstrated in Atlantic salmon [ 54 ].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A similar trend was observed in studies of Jian carp [ 55 ] and rainbow trout [ 13 ], fed H. illucens larva meal. The positive effect on HSI observed in the present study could be related to reduction of lipid storage in liver, as was demonstrated in Atlantic salmon [ 54 ].…”
Section: Discussionsupporting
confidence: 78%
“…The differences among studies could be related to diet composition. In the present study, as well as those of Borgogno et al [ 53 ] and Renna et al [ 15 ], fish oil was used as a fat source, while Belghit et al [ 54 ], used large quantities of rapeseed oil, which contain high level of n-6 polyunsaturated fatty acids contributing to maintain constant the n-3/n-6 ratio between insect meal based diets.…”
Section: Discussionmentioning
confidence: 61%
“…The SFA is the main FA in BSF derived oil and lauric acid (C12:0), palmitic acid (C16:0), and oleic acid (C18:1) are predominant FAs [4]. Moreover, the BSFL contains a high level of lauric acid which has an antimicrobial effect on gut pathogens [19][20][21]. Even though the partial replacement of BSFLO has shown no negative effects on growth performance and gut health, the BSFLO has a defect that alters the FA profile of the meat [6][7][8].…”
Section: Itemsmentioning
confidence: 99%
“…The apparent digestibility coefficients (ADC) of fatty acids were high (ADC > 95%) in Atlantic salmon fed an insect-based diet, where the lipid fraction was BSFL oil, which is rich in medium-chain fatty acids like lauric acid. The high content of lauric acid in the insect-based diets led to inhibited lipid storage in the fish liver [63]. The partial or total replacement of soybean oil with supercritical CO2 BSFL fat extract applied in young turkey poult had no adverse effect on the growth performance, nutrient digestibility or selected internal organ weights and lengths.…”
Section: Non-food Applications Of Bsfl Lipids: Biodieselmentioning
confidence: 98%